CURRENT APPROACHES TO THERAPY OF RETT’S SYNDROME (A REVIEW OF LITERATURE) - N. Yu. Borovikova; M. Yu. Bobylova (Русский журнал детской неврологии)
Antiepileptic therapy is one of the most urgent problems in the treatment of Rett’s syndrome. By taking into account a common concurrence of generalized and focal seizures with diffuse epileptiform activity on the electroencephalogram (EEG) in Rett’s syndrome, there are effective broad-spectrum antiepileptic drugs (AEDs): valproates, topiramate, levetiracetam, lamotrigine. Carbamazepine is effective for focal seizures and in the absence of diffuse EEG changes. For atypical absences, ethosuximide may be added to valproates, topiramate, or levetiracetam. Reflex seizures show a high resistance; their frequency is occasionally reduced by AEDs in combination with neuroleptics. Sleep hygiene, as well as medication (clonidine, zolpidem, trazodone, melatonin, risperidone) are recommended to correct various sleep disorders. Dopamine agonists, as well as L-carnitine are used for the drug correction of movement disorders in Rett’s syndrome. Therapeutic exercises are one of the most optimal ways to correct movement disorders. Orthopedic correction, including surgery, is indicated for skeletal deformities. Vitamin D used for long periods of time is beneficial, by considering its deficiency and osteoporosis at a fracture risk in Rett’s syndrome patients who receive AEDs particularly long. A special high-fat diet and a fractional diet in small portions are used in the therapy of cachexia and growth retardation due to oral dysfunction and malnutrition. A cardiological follow-up is needed in abnormalities, such as prolonged Q interval, tachyarrhythmia, and cardiac structural anomalies. Systematic learning to maintain communication and motor skills are of importance. In this case a special role is played by music therapy that exerts a calming effect on patients and partially compensates for loss of contact with the environment.